Experimental and numerical investigations on the performance of a G-PV/T system comparing with A-PV/T system. (1st March 2020) - Li, Zhaomeng; Ji, Jie; Yuan, Weiqi; Song, Zhiying; Ren, Xiao; Uddin, Md Muin; Luo, Kun; Zhao, Xudong
Abstract: PV/T systems are developed to obtain electrical & thermal energy simultaneously. Generally, in PV/T system where PV cells are laminated on absorbing plate (A-PV/T), the cells can be damaged due to high temperature, thermal stress, electrical insulation problem and absorbing plate deformation. Consequently, the reliability of PV cells limits the wide application of A-PV/T systems. Moreover, the electrical performance is affected by high cells' temperature. To overcome these problems, proposed a new structure of a PV/T system where cells are laminated on the back of glass cover (G-PV/T) instead. Experimental and numerical investigations are performed to explore the performance of two systems. The G-PV/T shows a lower temperature and better photovoltaic performance with the daily electrical efficiency of 11.66% (which of A-PV/T is 9.74%), thermal efficiency of 28.4%, and final water temperature of 45.6 °C. Two 3D dynamic thermal/electrical models are also proposed, which shows good agreement with experimental data. The influences of various structural parameters (PV coverage ratio, thickness of absorbing plate, thickness of air gap) on both PV/T systems have been predicted and compared. Furthermore, two mechanical models are proposed to explore the thermal stress distributions across the cells as well as provide an economic analysis of two systems. Highlights: A structure of G-PV/T system with cells laminated on the back of glass cover is proposed. It is experimental & numerical investigated and compared with A-PV/T system. The G-PV/T achieves better performance in temperature and electricity. The thermal stress on cells are simulated and the reliability of G-PV/T is improved. An economic analysis of two systems is provided.